Research of Braking Stability for Heavy Duty Wet Brake based on System Stability Degradation Algorithm - Xia Xiaohui (Jixie chuandong)
For the issues of heavy duty engineering vehicle wet brake poor stability during braking,the system stability degradation algorithm is introduced into the heavy wet brake stability evaluation system,the degradation data integration of the product components manufacturers and users are got by themselves,and the parameters of the leading role of the wet brake stability is determined based on sensitivity analysis. The stability evaluation accurate conclusion on design scheme in the initial design stage of wet brake is proposed and compared with the prototype test data. The results show that as the design of sensitive parameters information initial stability deviation and degradation information would take into consider,a heavy wet brake stability evaluation method is proposed based on the system stability degradation theory. Through this method,the efficiency of product design is greatly improved,the blindness of design is reduced,and play an important role in improving the production efficiency of the enterprise.